The New Encyclopaedia Britannica: Macropaedia: Knowledge in Depth: Volume 28: Spain Union (Chicago Encyclopaedia Britannica Inc., 1994)
32 v. : ill. (some col.), maps ; 29 cm. + Supplement.
v. 1-12. Micropaedia -- v. 13-29. Macropaedia -- [v. 30] Propaedia -- [v. 31-32] Index -- Supplement 1-2. Encyclopaedia Britannica Inc. Peter B. Norton, President and Chief Executive Officer Joseph J. Esposito, President, Publishing Group Chicago Auckland/London/Madrid/Manila/Paris/Rome/Seoul/Sydney/Tokyo/Toronto
Spine title: Britannica.
Keywords: Encyclopedias (3GdehShYGJs; General; Encyclopedias and dictionaries